Pengaruh Laba Akuntansi & Arus Kas Operasi Terhadap Keputusan Investasi (Return Saham): (Studi Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 ) - M. Rinto Ananta Pintarto; Pujiono Pujiono (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2021)
This study aimed to examine the market reaction to the publication of accounting information in the form of profits and operating cash flows associated with investment decisions. As a proxy of investment decisions is stock returns in banking companies at the time of publication of financial statements. The technique applied in this research is purposive sampling, obtained as many as 114 data (from 38 companies for 3 years). Using the SPSS tool. The method used in this research is non-linear regression test. The results of the study show that accounting earnings have an effect on investment decisions (stock returns), meanwhile operating cash flows doesn’t have any effect on investment decisions (stock returns). Therefore, it is recommended for investors to pay more attention to accounting income statements than operating cash flows to sort out stocks itself. keywords: accounting income, operating cash flow, stock returns, investment decisions.